Legionella pneumophila regulates the small GTPase Rab1 activity by reversible phosphorylcholination - Tan, Yunhao (National Academy of Sciences, 2011)
Effectors delivered into host cells by the Legionella pneumophila Dot/Icm type IV transporter are essential for the biogenesis of the specialized vacuole that permits its intracellular growth. The biochemical function of most of these effectors is unknown, making it difficult to assign their roles in the establishment of successful infection. We found that several yeast genes involved in membrane trafficking, including the small GTPase Ypt1, strongly suppress the cytotoxicity of Lpg0695(AnkX), a protein known to interfere severely with host vesicle trafficking when overexpressed. Mass spectrometry analysis of Rab1 purified from a yeast strain inducibly expressing AnkX revealed that this small GTPase is modified posttranslationally at Ser(76) by a phosphorylcholine moiety. Using cytidine diphosphate-choline as the donor for phosphorylcholine, AnkX catalyzes the transfer of phosphorylcholine to Rab1 in a filamentation-induced by cAMP(Fic) domain-dependent manner. Further, we found that the activity of AnkX is regulated by the Dot/Icm substrate Lpg0696(Lem3), which functions as a dephosphorylcholinase to reverse AnkX-mediated modification on Rab1. Phosphorylcholination interfered with Rab1 activity by making it less accessible to the bacterial GTPase activation protein LepB; this interference can be alleviated fully by Lem3. Our results reveal reversible phosphorylcholination as a mechanism for balanced modulation of host cellular processes by a bacterial pathogen.